Effect of Electroacupuncture on Platelet-derived Growth Factor and the Ultrastructure of Mitochondria in Rats with Diabetic Gastroparesis - Wei Xing; Peng Yan; Zhao Dong-Feng; Xiao Xiao-Juan; Lin Ya-Ping (KeAi Communications Co., Ltd., 2020)
Objective: To observe the effect of electroacupuncture (EA) at the pressure points Zu San Li (ST36), San Yin Jiao (SP6) and Liang Men (ST21) on platelet-derived growth factor (PDGF) and the ultrastructure of mitochondria in rats with diabetic gastroparesis (DGP). Methods: Sixty Sprague Dawley (SD) rats were randomly separated into a normal control group (NC, n = 10) and a modeling group (n = 50). Rats in the modeling group received an injection of 2% streptozotocin (STZ) and a high-fat and high-glucose diet for eight weeks to establish a DGP rat model. At the same time, blood glucose and a general symptom score were recorded every week. After modeling, 30 successfully modeled rats were randomly separated into the following groups: the DGP group (n = 10), the EA group (n = 10) and the metoclopramide (MP) group (n = 10). After three weeks of intervention, the gastrointestinal propulsive rate was measured by measuring the optical density (OD). The concentration of Ca2+ was determined by fluorescence immunoassay, and levels of serum insulin (INS) and PDGF were determined by ELISA. The ultrastructure of mitochondria was observed with transmission electron microscopy. Results: (1) After intervention, levels of blood glucose and the general symptom score were greatly decreased in the EA group compared to the DGP group (P < 0.01). Compared with the DGP group, the gastric emptying rate and the intestinal propulsive rate of the EA group was significantly improved (P < 0.01), and there was no statistically significant difference between the EA and the NC groups. (2) Compared with the NC group, the levels of INS in the DGP group markedly decreased (P < 0.05), but there was no significant difference of INS levels between the EA and the MP groups. (3) Compared with the DGP group, the concentration of Ca2+ in the EA and the MP groups significantly increased (P < 0.01, P < 0.05, respectively). (4) Compared with the NC group, the average OD of PDGF in the DGP group was significantly higher (P < 0.01). Compared with the DGP group, levels of PDGF in the EA group increased significantly (P < 0.01). (5) There were abundant mitochondria with a clear structure and complete cristae in the NC group. However, in the DGP group, mitochondria were severely swollen, partly vacuolated, and cristae were either fractured, absent, or shortened. In the EA group, mitochondria were slightly swollen, with clear cristae. Conclusions: Electroacupuncture at the points Zu San Li (ST36), San Yin Jiao (SP6) and Liang Men (ST21) may improve gastric motility in DGP by up-regulating the amount of PDGF and improving the ultrastructure of mitochondria. Keywords: Electroacupuncture (EA), Diabetic gastroparesis (DGP), Platelet-derived growth factor (PDGF), mitochondria, gastric motility